The Use of Human Dignity in Legal Argumentation: An Analysis of the Case Law of the Supreme Courts of Finland. Issue 3 (3rd July 2021) - Niemi, Hanna-Maria
ABSTRACT: The concept of human dignity is increasingly used in legal reasoning, albeit that we still lack a clear understanding of its function in that sphere. In European countries, its use is influenced by varying national and regional European applications in courts. This article conducts a theoretically oriented empirical analysis of the case law of the two supreme courts of Finland to canvass the use of human dignity in the argumentation of these courts. The analysis is based on 92 cases from the Supreme Administrative Court and 36 from the Supreme Court that refer to human dignity in the reasoning part of the judgement. Three different uses of human dignity in legal argumentation are recognised and defined: restrictive, enabling and compensatory. These uses are arguably also recognisable in other jurisdictions. However, the compensatory use of human dignity, in the context of tort law – in the form of damages for emotional suffering – in particular, appears not to have been extensively discussed before. The article argues that the different uses of human dignity in legal argumentation reflect many ideas traditionally connected with the concept. For example, the close connections between dignity and autonomy, and dignity and vulnerability, emerge from the case law.